Labelling Alpha-1 antitrypsin deficiency in the medical record – A call to action. (March 2022) - Riley, Leonard; Lascano, Jorge
Abstract: Alpha-1 antitrypsin deficiency (AATD) is an autosomal codominant genetic cause of chronic obstructive pulmonary disease (COPD) with over 100 allelic variants described. The normal allele is termed "M"; whereas, the "Z" and "S" alleles are the most common abnormal alleles. The ZZ combination accounts for 95% of cases with severe disease. We described the characteristics of patients given the label of AATD in the medical record. Our analysis found there is significant heterogeneity with regards to labelling subjects with AATD in the medical record, and this was true irrespective of the subjects age, gender, PFT measurements, tobacco pack years, or if the physician was a pulmonologist. In summary, this study highlights the need for continued investigation of the role of other mutations developing disease and options for more specific labelling of subjects with non-severe AATD and severe AATD to provide additional clarity for the patient and healthcare providers. Highlights: Severe alpha-1 antitrypsin deficiency is defined as a serum AAT levels ≤56 mg/dL. We describe a population of severe and non-severe AATD. Demonstrate that patients are mislabeled as AATD in the medical record. We propose severe and non-severe AATD terms for future research and patient care.